'Improving Advance Care Planning in Care Homes and other settings, as part of the Gold Standards Framework Training Programme. Issue 1 (1st June 2011) - Thomas, K; Stobbart-Rowlands, M; Giles, L
Abstract : Advance Care Planning (ACP) is a pivotal aspect of the Gold Standards Framework Care Homes Training Programme used by over 2000 care homes (aged care/long term facilities) in England. The key ACP standard to be attained for accreditation is that 'An ACP discussion is offered to and recorded for every resident and their families/carers.' Despite some initial barriers and difficulties in introducing this within this sector, a recent survey confirms that it is extremely successfully used, with considerable benefit for all. There will be an overview of GSF Care Homes Training Programme, describing lessons learnt, evidence of improvements in the confidence and effectiveness of staff, interviews with staff from accredited care homes describing their experiences and guidance on ACP with dementia patients. In the second half of this interactive workshop, we will be led by Prof Joanne Lynn to explore a challenging subject in your setting, discuss the difficulties and how some have been overcome. We will be supported to develop key aims, measures and changes to address ACP or another key problem. We will hear the experiences of others in this field and help provide practical suggestions for best practice in your area.